Advances of Spectrometric Techniques in Food Analysis and Authentication - Cozzolino, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint provides an overview of recent applications of both chemometrics and spectrometric techniques to target current issues associated with food authenticity, traceability, as well as modern approaches on the analysis of food ingredients and products.